Pengaruh Kompetensi Manajerial Kepala Sekolah, Motivasi Kerja dan Iklim Organisasi Terhadap Kompetensi Pedagogik Guru SMP Negeri Sekecamatan Wonosobo Kabupaten Wonosobo - Setyaningsih, Dwi; Egar, Ngasbun; Juliejantiningsih , Yovitha (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
All teachers must have pedagogical competence in managing learning in the classroom so that learning objectives can be achieved. The aim of this research is to: determine and analyze the influence of the principal's managerial competence, work motivation and organizational climate on teachers' pedagogical competence. The research approach used is quantitative. The population of this study was 138 teachers and the research sample was 103 teachers. Data collection was carried out using a questionnaire. The research results show that: 1) The influence of managerial competence on pedagogical competence is 64.6%, 2) The influence of work motivation on pedagogical competence is 75.8%, 3) the correlation between organizational climate and pedagogical competence is 0.902. 3) The influence of organizational climate on pedagogical competence is 81.4%, 4) The influence of managerial competence, work motivation and organizational climate on pedagogical competence is 83.1%. The conclusion of this research is that managerial competence, work motivation and organizational climate on pedagogical competence are 83.1%.